Effects of SAQ, HIIT, and SSG training on sprint and COD performance in soccer players: A pairwise and network meta-analysis - Niu, X.; Liu, F.; Liu, L.; Chen, Y.; Zhou, Z. (Kinesiology, 2025)
The objective was to systematically compare the effects of speed, agility, and quickness (SAQ) training, high-intensity interval training (HIIT), and small-sided games (SSG) training on sprint and change of direction (COD) performance in soccer players through pairwise and network meta-analyses. A comprehensive search of five electronic databases (PubMed, Web of Science, Embase, Cochrane, and EBSCO) was conducted during June 2025 to identify controlled trials involving SAQ, HIIT, or SSG training interventions. Studies meeting predefined eligibility criteria underwent pairwise meta-analysis (PMA) to calculate standardized mean differences (SMDs) against control conditions, and network meta-analysis (NMA) to estimate comparative efficacy across all three modalities. Surface under the cumulative ranking (SUCRA) values were computed to establish an intervention hierarchy. Twenty-three studies involving 914 participants were included. Pairwise meta-analysis (PMA) results showed that, compared with the control groups, only SAQ training significantly improved sprint (SMD = -1.23, 95% CI: -1.85 to -0.60, p<.001) and COD performance (SMD = -1.09, 95% CI: -1.69 to -0.48, p<.001). In network meta-analysis (NMA), SAQ ranked highest for sprint performance (SUCRA = 98.2%), followed by conventional training (CT) (57.0%), HIIT (36.7%), and SSG (8.1%). For COD performance, HIIT (SUCRA = 67.3%) ranked highest, followed by SSG (65.9%), SAQ (63.1%) and CT (3.7%). SAQ training demonstrated the most robust enhancement of sprint speed among the examined modalities. Although direct comparisons indicated benefits of SAQ for COD performance, its superiority was not confirmed in the network analysis, likely due to limited head-to-head data and study heterogeneity. A training strategy centered on SAQ, with supplemental HIIT and SSG components, is therefore recommended to optimize both sprint and COD adaptations in soccer players.